2008
DOI: 10.1080/13550280802337217
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of retinoic acid–inducible gene-I expression in primary murine glia following exposure to vesicular stomatitis virus

Abstract: Vesicular stomatitis virus (VSV) is a negative-sense single-stranded RNA virus that closely resembles its deadly cousin, rabies virus. In mice, VSV elicits a rapid and severe T cell–independent encephalitis, indicating that resident glial cells play an important role in the initiation of central nervous system (CNS) inflammation. Recently, retinoic acid–inducible gene I (RIG-I)-like helicases have been shown to function as intracellular pattern recognition receptors for replicative viral RNA motifs. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…In this study, we observed that LGP2 expression is tightly regulated and not ubiquitous, as previously suggested (11,17,30). Remarkably, in the absence of infection, neurons and microglia express low levels of LGP2 protein, if they express any, with the exception of ex vivo primary astrocytes in cultures (11,17).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In this study, we observed that LGP2 expression is tightly regulated and not ubiquitous, as previously suggested (11,17,30). Remarkably, in the absence of infection, neurons and microglia express low levels of LGP2 protein, if they express any, with the exception of ex vivo primary astrocytes in cultures (11,17).…”
Section: Discussionsupporting
confidence: 49%
“…Remarkably, in the absence of infection, neurons and microglia express low levels of LGP2 protein, if they express any, with the exception of ex vivo primary astrocytes in cultures (11,17). In the LGP2 TG mouse, LGP2 protein expression reached the lowest level in the brain compared with other tissues, despite similar LGP2 transcription levels.…”
Section: Discussionmentioning
confidence: 99%
“…The brain possesses functional RLR and TLR systems (3,23), and constitutive expression as well as upregulation of both systems in response to virus infection was previously described for astrocytes (24,25). Using mice with defects in the known innate signaling pathways, we analyzed which sensors might determine IFN-␤ synthesis in the virus-infected brain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is becoming apparent that there are TLR-independent mechanisms of virus sensing. The cytoplasmic helicase retinoic acid inducible gene-I (RIG-I) and melanoma differentiation-associated gene 5 (MDA5) recognize viral nucleic acids and are essential for the production of type I interferons and inflammatory cytokines in the context of viral infection (Kawai and Akira, 2006;Kato et al, 2008;Furr et al, 2008Furr et al, , 2010. In addition to a role in antiviral responses, recent studies have demonstrated that RIG-I and MDA5 play an important role in regulation of the expression of inflammatory cytokines and IFITM3 NM_025378 GCCTATGCCTACTCCGTGAAGT GCCTGGGCTCCAGTCACAT TLR3 NM_126166 TCATTTTCGTTATCACACACCATTT TGAACTGCGTGATGTACCTTGAA TLR4 NM_021297 TCAGAACTTCAGTGGCTGGATTT ATGCCATGCCTTGTCTTCAATT RIG-I NM_172689 GCGTGCTACACAGCTGACATTC AGCGTCTCCAAGGACAGTGTAGT MDA5 NM_001164477 ATGAAACCAGAGGAGTATGCACATAA TGCTTTGCAATGCTTCTTTTGA IFN-b NM_010510 AGCTCCAAGAAAGGACGAACAT GCCCTGTAGGTGAGGTTGATCT TNF-a NM_013693 GCCAGCCGATGGGTTGT GCAGCCTTGTCCCTTGAAGA IL-1b NM_008361 TCCACCTCAATGGACAGAATATCA GGTTCTCCTTGTACAAAGCTCATG IL-6 NM_031168 AACGATGATGCACTTGCAGA TGGTACTCCAGAAGACCAGAGG IL-10 NM_010548 AGCTGAAGACCCTCAGGATG TGGCCTTGTAGACACCTTGG b-Actin NM_007393 CGATGCCCTGAGGCTCTTT TGGATGCCACAGGATTCCA IFITM3 (interferon-induced transmembrane protein 3), TLR3 (toll-like receptor 3), TLR4 (toll-like receptor 4), RIG-I (retinoic acid-inducible gene-I), MDA5 (melanoma differentiation-associated protein 5), IFN-β (interferon-β), TNF-α (tumor necrosis factor-α), IL-1β (interleukin-1β), IL-6 (interleukin-6), IL-10 (interleukin-10).…”
Section: Introductionmentioning
confidence: 99%